IDENTIFICATION AND PREVALENCE OF GASTROINTESTINAL PROTOZOA IN PIGLETS THAT SOLD IN A TRADITIONAL MARKET IN BALI - Agustina, Kadek Karang; Sudewi, Ni Made Ayudiningsih Astiti; Dharmayudha, Anak Agung Gde Oka; Oka, Ida Bagus Made (Buletin Veteriner Udayana, 2016)
This research aims were to determine the type and prevalence of infections of gastrointestinal protozoan in piglets were sold in the pig traditional markets in Bali. As many as 250 piglets fecal samples were examined. All fecal samples were taken in a fresh state and then divided in two different sollution, one stored in plastic pots containing acetic sodium formaldehyde (SAF) for examination by sedimentation concentration method and another samples were stored in plastic pots containing potassium dichromate for examination by the method of floating. Samples were examined microscopically for the presence of cysts or oocystsof gastrointestinal protozoa. The results showed that 229 (91.6%) piglets were sold in the pigtraditional markets in Bali  infected by protozoa, and identified three Genus of protozoa with following prevalence of infection were Amoeba sp. 82.4%, Balantidium sp. 61.2% and Eimeria sp. 54.8%.
Keywords: prevalence; gastrointestinal protozoa; piglets; traditional markets